The rhythm of cognition: older adulthood edition - McDermott, Cynthia, author; Bielak, Allison, advisor; Fenton, Melissa, advisor; Broussard, Josiane, committee member (Colorado State University. Libraries, 2024)
Circadian rhythm is a delicate function that regulates multiple processes, such as cognition, sleep, and appetite. As humans age, their circadian rhythms shift to become earlier, resulting in their cognitive peak performance being earlier in the day. This study's main goals were to investigate if older adults (N = 139; Mage = 69.22; range = 60-89) who completed online cognitive tasks over 7 days at peak hours performed better than those who completed them at off-peak hours, as well as to determine if there were specific cognitive tasks that older adults did better on during these peak times. Four cognitive tasks were used to measure working memory, inductive reasoning, episodic memory, and processing speed. As tested by Repeated Measures Analysis of Variance (RMANOVA), results showed no significant between-group differences, which indicated that the different test timing groups did not differ in their cognitive performance. The RMANOVA results also revealed no significant effects of test timing groups for any of the individual cognitive tasks. These findings are inconsistent with the little research available regarding on- and off-peak test timing in older adults and suggest the need for a more well-controlled study focused on older adults. If a more reliable on-peak test time for older participants is identified, then clinicians who test cognition could have the ability to detect cognitive decline earlier on. Ultimately, this could lead to earlier diagnoses or recognition of abnormal changes in cognition.